Anaerobic metabolism of two hydro‐morphological similar pre‐dams under contrasting nutrient loading (Rappbode Reservoir System, Germany). Issue 5 (October 2014) - Wendt‐Potthoff, Katrin; Kloß, Christin; Schultze, Martin; Koschorreck, Matthias
<x xml:space="preserve">Abstract</x> Anaerobic microbial processes in reservoirs have a strong influence on water quality, and these processes are influenced by inputs from the catchment. Two morphologically similar pre‐dams of the large Rappbode reservoir system in Germany were studied for oxygen consumption, carbon dioxide production, nitrate reduction, manganese and iron reduction, sulfate reduction, and methanogenesis. Rates were obtained by calculations from hypolimnion size and hypolimnetic water chemistry and from incubation of sediment samples (manganese and iron reduction, sulfate reduction, and methanogenesis only). Length of anoxic conditions (anoxic factor) and anaerobic process rates were generally higher for Hassel pre‐dam, a water body with 58% grasslands and agriculture in its catchment. Rappbode pre‐dam had higher iron reduction rates. Oxygen consumption and sulfate reduction (and nitrate reduction for Hassel pre‐dam) were the most important respiratory processes. While hypolimnion chemistry was similar and showed mainly temporal differences in seasonal development, the pre‐dam sediments differed considerably with roughly twofold higher microbial biomass and 102–104 fold higher counts of sulfate‐reducing prokaryotes in Hassel pre‐dam compared to Rappbode pre‐dam. These differences can be explained by the higher nutrient input, longer water retention time, and consequently higher biomass production in Hassel pre‐dam. The view of microbial activities against known loads of solutes also implies that the quality of allochthonous organic matter and particulate fluxes likely governs respiratory processes in the pre‐dams by providing electron donors and acceptors.